TRANSITIVITAS DALAM KUMPULAN CERPEN SEPASANG SEPATU TUA KARYA SAPARDI DJOKO DAMONO (KAJIAN LINGUISTIK SISTEMIK FUNGSIONAL) - Agnes Gabril; Anshari Anshari; Mahmudah Mahfud (Fakultas Bahasa dan Sastra Indoensia, 2024)
This research aims to analyze the form of transitivity in the short story collection A Pair of Old Shoes by Sapardi Djoko Damono. This research uses qualitative research by applying descriptive methods. The results of the research show that the short story A Pair of Old Shoes uses six forms of transitivity, namely six processes and the most dominant form of transitivity used is mental transitivity. Based on the use of mental processes, the short story A Pair of Old Shoes invites readers to participate in feeling, seeing, imagining and thinking about the events and actions experienced and accepted by the characters in the short story